HbA1c as a screening tool for diabetes mellitus and its use with traditional and novel biochemical parameters to predict cardiovascular risk in a local urban community - Zemlin, Annalise E. (Stellenbosch : Stellenbosh University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.